Early Commencement of Enteral Feeds in Gastroschisis: A Systematic Review of Literature - Dama, Madhuri; Rao, Uday; Gollow, Ian; Bulsara, Max; Rao, Shripada (European Journal of Pediatric Surgery, 2017)
Introduction There are no evidence-based strategies to improve feed tolerance in gastroschisis. Early commencement of enteral feeds (CEF) is known to improve feed tolerance in preterm infants. It is possible that infants with gastroschisis may also benefit from early CEF.Objective To conduct a systematic review to evaluate the relationship between time of CEF, and time to reach full enteral feeds (FEF), duration of parenteral nutrition (PN), and duration of hospital stay (HS).Methods PubMed, EMBASE, Cochrane CENTRAL, and relevant conference abstracts were searched in December 2015. Studies of any design reporting on time to CEF and one or more of the outcomes of interest were included. Meta-regression analysis was conducted to find the association between time to CEF and the outcomes of interest.Results There were no randomized controlled trials (RCTs) comparing early (≤7 days from birth) versus delayed (>7 days) CEF. Forty-two observational studies on gastroschisis (4,835 infants) where feed-related information was available were included. Meta-regression results indicated that each day delay in CEF was associated with a delay of an additional 1.4 days (95% confidence interval [CI]: 0.95, 1.85) to FEF, 2.05 days (95% CI: 1.50, 2.59) to the duration of PN, and 1.91 days (95% CI: 1.37, 2.45) to the duration of HS. Sensitivity analysis after excluding studies that provided information exclusively on complex gastroschisis continued to show beneficial effects of early CEF.Conclusion Early CEF may be associated with early attainment of FEF in gastroschisis. RCTs comparing early versus delayed CEF are needed urgently.
Keywords: systematic review; feed intolerance; abdominal wall defect; parenteral nutrition